KONSEP KEMA’SHUMAN NABI SAW.: Tafsir Ayat-Ayat ‘Itāb dalam Tafsir Al-Ibriz - Rohmaniyah, Rizqi; Robi’ Nur Muhammad, Alfet (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2024)
This research discusses the concept of the Infallibility of the Prophet Muhammad SAW from the perspective of the Indonesian commentator, namely KH. Bisri Mustofa in Tafsir Al-Ibriz. Prophet Muhammad SAW is a person who is protected by Allah from all forms of sin. However, in several incidents, Allah SWT rebuked the attitudes and decisions taken by the Prophet Muhammad SAW through verses from the Koran. This gives a negative impression of the ma'sum nature bestowed by Him. This is proven by the revelation of the 'Itāb verses addressed to the Prophet Muhammad SAW to straighten out his attitude. This research is a qualitative type of research that is a literature study. The conclusion of this research is KH. Bisri Mustofa is a figure who really respects and glorifies the Prophet Muhammad SAW. So, in interpreting the 'Itāb verse, he really paid attention to the language used so as not to lower the self-esteem of the Prophet Muhammad SAW. The Prophet Muhammad was protected from mistakes and sins, but the Prophet Muhammad SAW was still an ordinary human being who never made mistakes in taking action. Keywords: ma’shum, ayat ‘thab, Ibriz